BRANDING ACTIVATION AS A SUSTAINABLE IMAGE BUILDING PROCESS: ANALYSIS OF EVENTS BY SEJAUH MATA MEMANDANG - Ayuningtias Ramadhani; Agung Eko Budiwaspada (Gorga : Jurnal Seni Rupa, 2024)
Branding activation is part of the branding strategy in building and communicating the identity and values of a brand. This branding activation functions as a tool to interact directly with consumers through various activities such as events. Events are one of a series of branding activations because they have a direct connection with consumers, allowing for deeper and more personal interactions for brands to convey their image. In the context of sustainable branding, branding activation is a process that only aims to convey environmental, social, and economic values, but also to build deeper relationships with consumers by emphasizing the brand's commitment to sustainable practices. Through semiotic analysis, this research explores the role of branding activation in forming and communicating a sustainable brand image, with a focus on the "Kedai Kita" event by Sejauh Mata Memandang. The image of a brand can be formed through the meaning conveyed by visual elements which function to communicate certain messages to the audience through the meaning that is present. This research examines how these elements reflect a brand's commitment to sustainability. Seeing how Sejauh Mata Memandang can process through its branding activation conveys a sustainable image at the event. These findings show how Sejauh Mata Memandang effectively utilizes event branding activation as a strategic tool to convey a sustainable brand image through the immediacy of everyday life while raising awareness about the threat of climate change to our food sources.